FASE-FASE PENDIDIKAN DALAM PERSPEKTIF HADIS - Hana Zulfahmi Ma'rifatullah; Asma Mangar (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Ar-Rahman, 2025)
This study examines the stages of education from the perspective of prophetic teachings that emphasize a gradual and developmentally appropriate approach to nurturing children. The core issue addressed in this research is the need for an educational framework that aligns intellectual, moral, and spiritual growth with the natural phases of human development. The study aims to explore how the prophetic guidance regarding the command to perform prayer at specific ages reflects a structured model of education that corresponds to children’s cognitive and emotional readiness. Using a qualitative method with a literature-based approach, this research analyzes classical texts, contemporary scholarly works, and educational theories to construct a comprehensive understanding of the stages of learning in early Islamic tradition. The findings reveal that education in this perspective unfolds through four interconnected phases: the stage of value internalization through exemplary behavior, the stage of habituation and comprehension, the stage of reinforcement through discipline, and the stage of independence and spiritual awareness. These phases illustrate an educational process that progresses from imitation to conscious practice and moral responsibility. The study concludes that the prophetic model presents a holistic and sustainable educational framework that harmonizes spiritual formation with psychological development, offering valuable insights for modern educational systems seeking to cultivate individuals who are intellectually capable, morally grounded, and spiritually conscious.